1997
DOI: 10.1139/a97-004
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of environmental and other factors in some recent marine mammal mortalities in Europe: implications for conservation and management

Abstract: Major mortality events in marine mammal populations have become a feature of recent years and their causes have been much debated. Here we review the investigations that have been made to date into the 1988 seal epizootic in the North Sea region, the 1990-1992 striped dolphin epizootic in the Mediterranean Sea, and the recent spate of sperm whale strandings in the northeastern Atlantic. We consider the evidence for multifactorial causality in these events and the problems inherent in determining causes. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…An example is the die-off of striped dolphins Stenella coeruleoalba that spread across the entire Mediterranean in the 1990s and resulted in the loss of thousands of animals. The poor nutritional state of the dolphins resulting from low nutrient input to the eastern Mediterranean, caused originally by abnormally low rainfall, may have been a precipitating factor (Simmonds & Mayer, 1997).…”
Section: Speciesmentioning
confidence: 99%
“…An example is the die-off of striped dolphins Stenella coeruleoalba that spread across the entire Mediterranean in the 1990s and resulted in the loss of thousands of animals. The poor nutritional state of the dolphins resulting from low nutrient input to the eastern Mediterranean, caused originally by abnormally low rainfall, may have been a precipitating factor (Simmonds & Mayer, 1997).…”
Section: Speciesmentioning
confidence: 99%
“…In some cases, alterations in migration paths could move animals into dangerous areas. For example, Simmonds & Mayer (1997) suggested that seismic surveys being conducted to the west of the British Isles might have contributed to recent live multiple sperm whale strandings in the North Sea if they caused southwardmoving animals to divert to the east of their normal course and into the shallow North Sea. As discussed above, information from recent mass strandings of beaked whales (e.g., Jepson et al, 2003) hints at the possibility that noise-induced changes in behavior could lead deep diving cetaceans to develop decompression sickness.…”
Section: Biological Significance Of Possible Effects Of Seismic Pulsementioning
confidence: 99%
“…This phenomenon resulted in reduced nutrient input into the eastern Mediterranean and thus low productivity (Simmonds & Mayer, 1997). This led to the decline of the dolphin's common prey and explains why many of the dolphin carcasses showed depleted body fat reserves (Aguilar et al, 1991).…”
Section: Change In Food Supplymentioning
confidence: 99%
“…Planque & Taylor, 1998;Waluda et al, 2001;Walther et al, 2002) affecting cetaceans like minke whales (Bjorge, 2002) Continued environmental threats to mediterranean cetaceans Mediterranean monk seal (Monachus monachus) ( Van de Bildt et al, 1999). A worldwide increase in mass mortality events in marine mammals has been reported by Simmonds & Mayer (1997). It is interesting to note that, as cetaceans are long-lived, slow-reproducing animals (generally producing one offspring per female every 2-3 years), when a population is severely diminished by a virus or other agents, recovery may be slow and such species can relatively easily become endangered (Dhermain et al, 2002;Reeves et al, 2003).…”
Section: Change In Food Supplymentioning
confidence: 99%